Tear Cathepsin S as a Candidate Biomarker for Sjögren's Syndrome. Issue 7 (July 2014) - Hamm‐Alvarez, Sarah F.; Janga, Srikanth R.; Edman, Maria C.; Madrigal, Sara; Shah, Mihir; Frousiakis, Starleen E.; Renduchintala, Kavita; Zhu, Jay; Bricel, Seth; Silka, Kimberly; Bach, Dianne; Heur, Martin; et al.
<x xml:space="preserve">Abstract</x> Objective The diagnosis of Sjögren's syndrome (SS) in routine practice is largely a clinical one and requires a high index of suspicion by the treating physician. This great dependence on clinical judgment frequently leads to delayed diagnosis or misdiagnosis. Tear protein profiles have been proposed as simple and reliable biomarkers for the diagnosis of SS. Given that cathepsin S activity is increased in the lacrimal glands and tears of NOD mice (a murine model of SS), the aim of this study was to explore the clinical utility of using tear cathepsin S (CTSS) activity as a biomarker for SS. Methods A method to measure CTSS activity in tears eluted from Schirmer's test strips was developed and validated. Schirmer's tests were performed and CTSS activity measurements were obtained in 278 female subjects, including 73 with SS, 79 with rheumatoid arthritis, 40 with systemic lupus erythematosus, 10 with blepharitis, 31 with nonspecific dry eye disease, and 12 with other autoimmune diseases, as well as 33 healthy control subjects. Results The median tear CTSS activity in patients with SS was 4.1‐fold higher than that in patients with other autoimmune diseases, 2.1‐fold higher than that in patients with nonspecific dry eye disease, and 41.1‐fold higher than that in healthy control subjects. Tear CTSS levels were equally elevated in patients with primary SS and those with secondary SS, independent of the Schirmer's test strip values or the levels of circulating anti‐SSA or anti‐SSB antibodies. Conclusion Markedly high levels of tear CTSS activity are suggestive of SS. CTSS activity in tears can be measured in a simple, quick, economical, and noninvasive manner and may serve as a novel biomarker for autoimmune dacryoadenitis during the diagnostic evaluation for SS.